For Eyes That Listen - Fereli, Melih; Evren, Süreyyya (Istanbul : Arter, 2021)
Beuys, Joseph ; Bloom, Barbara ; Cage, John ; Christiansen, Henning ; Dinç, Osman ; Driscoll, John ; Friðfinnsson, Hreinn ; Higgins, Dick ; Koller, Julius ; Kozłowski, Jarosław ; Kuhn, Hans Peter ; Onur, Füsun ; Paik, Nam June ; Adler-Petersen, Lene ; Ruenzler, Annette ; Santos, Carles ; Snow, Michael
boek